The quest for the understanding of Religious Studies: Seeing dragons - Beyers, Jaco (Verbum et ecclesia, 2016)
Religious Studies is concerned with studying religion or the absence thereof. The concept of religion has been discussed, disliked and dissected over centuries. Some have predicted the disappearance of religion, others have predicted the changing of location from the public to the private sphere and some even the re-emergence of religion. In trying to determine the place and relations of Religious Studies an understanding of what religion entails is necessary. It is clear that Religious Studies consists of a multiform subject field and a variety of disciplines with a multiplicity of issues, interests and topics together with a wide variety of approaches and methods. Some scholars have described religion as a saturated phenomenon' trying to indicate how the diversity of elements described as religious came to shroud the true subject matter. All these hindrances on the road to comprehending religion are like dragons preventing one from completing a (holy!) quest. This article does not want to provide new answers to an old debate. In this sense this article is not an attempt at slaying the dragons but identifying them. Three issues (dragons) are discussed. How religion, the object of Religious Studies, should be viewed? What methods are employed by Religious Studies and the relatedness of Religious Studies to Theology? In the end the article wants to provide direction on how Religious Studies, as academic discipline, can collaborate with research in Theology.Intradisciplinary and/or interdisciplinary implications: This article discusses the development of the subject of Religious Studies by providing a historic overview of sociological influences on the development. In this sense this article is not an attempt at slaying the dragons but identifying them. Three issues (dragons) are discussed: how religion, the object of Religious Studies, should be viewed; what methods are employed by Religious Studies and the relatedness of Religious Studies to Theology (with implications for interdisciplinary collaboration). In the end the article wants to provide direction in how Religious Studies as academic discipline can collaborate with research in Theology